Remarks on the church in the consumer society: similarities and dissimilarities - Lategan, L. O. K. (Faculty of Theology, University of the Free State, 2004)
The church cannot escape the influence of the consumer society. The influence of the consumer society is often viewed as negative although it can have many positive influences on the building and growth of the church. The consumer society reminds the church that, although the message of the church cannot change, the style of church services can. Pastors should make it clear that the gospel message is not a product for sale; however the gospel message should be directed at the needs of people. This article outlines the influence of the consumer society on the church. The article also outlines the similarities and dissimilarities between the church and the consumer society. It concludes with guidelines on how the church can bring its gospel message regardless the dominant influences of the consumer society.
Keywords: Ministry; Consumer society; Preaching